Metal(loid) and isotopic tracing of Pb in soils, road and house dusts from the industrial area of Volos (central Greece) - Kelepertzis, Efstratios; Argyraki, Ariadne; Chrastný, Vladislav; Botsou, Fotini; Skordas, Konstantinos; Komárek, Michael; Fouskas, Aggelos (The Science of the total environment, 2020)
This study examines the metal(loid) contents (As, Cd, Cr, Cu, Mn, Ni, Pb, Sb, Tl and Zn) and Pb isotopes in different environmental compartments (soil, road dust, house dust) from the industrial vicinity of Volos, central Greece. The area surrounding two steel factories, a cement plant, an industrial area and the city core were considered as potential hot spots of metal(loid) contamination. Significant anthropogenic enrichments of Cd, Pb and Zn in relation to local baseline were identified for the soil (median Enrichment Factors of 7, 15 and 8, respectively) and road dusts around the steel factory located at Velestino area. The high contents of As, Sb and Tl in the soil and road dust around the cement plant are attributed to natural sources of contamination associated with adjacent mineralization. The soil samples in the city core exhibited moderate enrichments with respect to typical tracers (Pb, Zn) of anthropogenic contamination in urban areas. Anthropogenic influences in terms of metal(loid) concentrations were more pronounced for the road and house dust material. The Pb isotopic ratios of soil (206Pb/207Pb = 1.154 to 1.194), road dust (206Pb/207Pb = 1.144 to 1.174) and house dust (206Pb/207Pb = 1.129 to 1.171) were between those of the local bedrock and anthropogenic Pb sources. Industrial Pb from the steel plant was the predominant anthropogenic Pb source with relative contributions of ~49% for the soil, ~42% for the road dust and ~44% for the house dust samples. For the road and house dust material, the geochemical signature obtained from Pb isotopic compositions and elemental ratios suggests additional contributors from vehicular emissions. The results of this study demonstrate the suitability of soil to trace natural and anthropogenic impacts in industrial areas and the sensitivity of the road and house dust material to record anthropogenic (industrial and vehicular-derived) contamination in such environments.
Keywords: Cement factory; Source identification; Potentially toxic elements; Lead isotopes; Steel plants